Decolonising the curriculum beyond the surge: Conceptualisation, positionality and conduct. (14th July 2021) - Abu Moghli, Mai; Kadiwal, Laila
Abstract : page_1 other In recent years, there has been increased interest in, and work towards, decolonising the curriculum in higher education institutions in the UK. There are various initiatives to review university syllabuses and identify alternative literature. However, there is an increasing risk of turning 'decolonisation' into a buzz term tied to a trend. We fear that decolonisation within academia is becoming an empty term, diluted and depoliticised, allowing for superficial representations that fail to address racial, political and socio-economic intersectionalities. In this article, we examine several initiatives to decolonise the curriculum with a focus on the field of education as a discipline and medium. Based on our analysis, we engage with three main themes: conceptualisation, positionality and conduct . The article concludes that decolonisation cannot happen in a vacuum, or as an aim disconnected from the rest of the structure of the university, which leads to diluting a wider movement and turns into a box-ticking exercise. We argue that there needs to be a deconstruction of asymmetrical power relationships within academic spaces to allow for meaningful decolonisation in practice. This requires a real political will, a change in the structure, and in the hearts and minds of those in decision-making positions, and a shift in the practices of knowledge production.